The effects of television and Internet food advertising on parents and children - Pettigrew, Simone; Tarabashkina, L.; Roberts, M.; Quester, P.; Chapman, K.; Miller, C. (Cambridge University Press, 2013)
Objective: The current study examined the impact of television and Internet food advertising on Australian parents and children.Design: Parents and their children aged 8 to 14 years were exposed to a television advertisement, an Internet advertisement or a control picture for four commonly advertised energy-dense, nutrient-poor foods.Setting: Online web panel survey, Australia.Subjects: Parents (n 1302) and their children aged 8 to 14 years (n 1302).Results: After a single exposure to each advertisement, parent respondents in the two exposure conditions evaluated the products more favourably, had a greater desire to consume the products and thought the product could be consumed more frequently than those in the control condition. Similar trends were observed among children, although the differences were statistically significant only for thefrequency of food consumption in the Internet advertisement condition and the evaluation of one product.Conclusions: The results have implications for assumptions of adults’ immunity to advertising. This is of particular importance in efforts to address child obesity and the reliance on parents to mediate the effects of food advertising.